PENGARUH BIAYA BAHAN BAKU DAN BIAYA TENAGA KERJA LANGSUNG TERHADAP PENJUALAN BERSIH PADA PT MUSTIKA RATU TBK - Sugiarti, Sugiarti (Yayasan Akrab Pekanbaru, 2018)
The aims of this study are to analyze the cost of raw materials and direct labor costs to net sales using multiple linear determination and regression. Data collection methods in the preparation of the Final Project are observation and study documentation with the method of analysis in the form of quantitative analysis of data analysis methods using statistical analysis. The data used are secondary data obtained from the website of PT Mustika Ratu Tbk. From the results of partial determination test (T test) obtained raw material cost significantly influence on net sales, that is equal to 78.6%. Likewise with direct labor costs significant effect on net sales, which amounted to 32.4%. The result of simultaneous determination test (F test) obtained the cost of raw material and direct labor cost have significant influence to net sales, that is equal to 91,5% and the remaining 8,5% influenced by other variable. The regression equation formed is Y = 3,688 + 0,736 X1 + 0,176 X2. Keywords: Raw Material Cost, Direct Labor Cost, Net Sales